The politics of schools and money: Building awareness about channeling practices for supplemental resource allocations to serve English language learners - Okhremtchouk, Irina (Education Policy Analysis Archives, 2017)
One of the aims of K-12 supplemental programs is to maximize the potential for success of students who bring special needs into a classroom. Therefore, the intent behind a large majority of these additional resources is to support programs that are designed to address the needs of otherwise marginalized students by leveling the playing field. The purpose of this work is to shed light on how supplemental funds are potentially channeled from the source to the students for whom these funds are intended and whose needs these funds intend to serve. Specifically, this article draws attention to the dynamics associated with channeling practices of supplemental dollars for English language learners. This article concludes with a practical discussion to offer insights for navigating the typical channeling practices of these funding streams.